2020
DOI: 10.1186/s12872-020-01436-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of miR-92a-3p, oxidative stress, and p38MAPK/NF-κB pathway in rats with central venous catheter related thrombosis

Abstract: Background: miR-92a-3p and oxidative stress are reportedly associated with venous thrombosis. However, the role of miR-92a-3p and oxidative stress in catheter-related thrombosis (CRT) remains ambiguous. Herein, we studied the roles of miR-92a-3p, oxidative stress, and p38-mitogen-activated protein kinase/nuclear factor kappa-B (MAPK/NF-κB) pathway in CRT. Methods: Forty-five male rats were randomly and equally divided into control, sham operation, and CRT groups. The rats were sacrificed after 10 days. Reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…As resistance exercise training may also affect the target genes of OS and cardiovascular autonomic function, the current research status of the correlation between miRNAs and CRT diseases should be further verified. The latest research results of our team 81 have confirmed that miR-92a-3p and OS are related to venous thrombosis. The expression levels of venous miR-92a-3p, HO-1, p38 MAPK, and NF-κB p65 mRNA in the CRT group were significantly upregulated, and miR-92a-3p was positively correlated with HO-1 (r = 0.770, P = .015).…”
Section: Regulation Of Mirna By Resistance Exercise To Prevent Crtmentioning
confidence: 60%
“…As resistance exercise training may also affect the target genes of OS and cardiovascular autonomic function, the current research status of the correlation between miRNAs and CRT diseases should be further verified. The latest research results of our team 81 have confirmed that miR-92a-3p and OS are related to venous thrombosis. The expression levels of venous miR-92a-3p, HO-1, p38 MAPK, and NF-κB p65 mRNA in the CRT group were significantly upregulated, and miR-92a-3p was positively correlated with HO-1 (r = 0.770, P = .015).…”
Section: Regulation Of Mirna By Resistance Exercise To Prevent Crtmentioning
confidence: 60%
“…The occurrence and development of CVC-related complications are related to oxidative stress and vascular endothelial damage caused by CVC. Gan et al found that CVC caused a significant increase in serum ROS and MDA levels in a rat model [ 34 ]. Other study has also shown that oxidative stress markers were predictors of CVC-related high-risk thrombosis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, platelet activation was ruled out; however, the clotting system may be involved in CRT formation. We monitored thrombus formation at different time periods spanning 14 days and at the end of 2 months [ 22 ]. We will continue examining changes in thrombus formation at different time periods for 1 month under resistance exercise intervention.…”
Section: Discussionmentioning
confidence: 99%
“…However, the signalling pathway that initiates CRT-induced oxidative stress injury in rats remains unclear. Gan's research [ 22 ] shows that HO-1 may be the target of miR-92a-3p and p38 MAPK/NF-κB pathway. miR-92a-3p may regulate HO-1/p38 MAPK/NF-κB pathway and result in CRT.…”
Section: Introductionmentioning
confidence: 99%